[tex](x+3)(x+2)=0[/tex] ↔ zero product property and
[tex](x+3)(x+2)=0[/tex] ↔ square root property.
Solution:
Given expressions are [tex](x+3)(x+2)=0[/tex] and [tex]x^{2}+6=31[/tex].
To find which techniques is most appropriate to solve each equation.
Equation 1: [tex](x+3)(x+2)=0[/tex]
Zero product property states that if AB = 0 then A = 0 or B = 0.
In the equation is [tex](x+3)(x+2)=0[/tex], zero product property is used to solve the equation.
(x + 3) = 0 (or) (x + 2) = 0
x = –3 (or) x = –2
Equation 2: [tex]x^{2}+6=31[/tex]
Subtract 6 from both sides of the equation.
[tex]x^{2}+6-6=31-6[/tex]
[tex]x^{2}=25[/tex]
[tex]x^{2}=5^2[/tex]
Take square root on both sides of the equation.
x = 5
Square root property is used to solve the equation.
Hence [tex](x+3)(x+2)=0[/tex] ↔ zero product property and
[tex](x+3)(x+2)=0[/tex] ↔ square root property.